2012
DOI: 10.1186/1471-2180-12-s1-s13
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and recombination in Wolbachia and Cardinium from Bryobia spider mites

Abstract: BackgroundWolbachia and Cardinium are endosymbiotic bacteria infecting many arthropods and manipulating host reproduction. Although these bacteria are maternally transmitted, incongruencies between phylogenies of host and parasite suggest an additional role for occasional horizontal transmission. Consistent with this view is the strong evidence for recombination in Wolbachia, although it is less clear to what extent recombination drives diversification within single host species and genera. Furthermore, little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 87 publications
4
32
1
Order By: Relevance
“…Although, recently Ros et al (2012) showed that recombination of Wolbachia with Cardinium in Bryovia spider mite that also similar with present findings about endosymbiont harbored in E. formosa.…”
Section: Discussionsupporting
confidence: 92%
“…Although, recently Ros et al (2012) showed that recombination of Wolbachia with Cardinium in Bryovia spider mite that also similar with present findings about endosymbiont harbored in E. formosa.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, many mite species were reported to harbor this symbiont (Duron et al 2008;Ros et al 2012;Kopecky et al 2013;Famah Sourassou et al 2014;Weinert et al 2015;Chaisiri et al 2015). There are several studies reporting Cardinium-induced reproductive alterations in mites (Weeks & Stouthamer 2004;Groot & Breeuwer 2006;Gotoh et al 2007;Ros & Breeuwer 2009;Liu et al 2010;Xie et al 2010;Wu & Hoy 2012;Zhu et al 2012b;Zhao et al 2013a;Zhao et al 2013b;Famah Sourassou et al 2014), and Cardinium seem to be essential for oviposition in the Ghana population of Neoseiulus paepalivorus (Famah Sourassou et al 2014).…”
Section: Reviewmentioning
confidence: 99%
“…Thus, the detection of its presence in mites is done mainly using PCR-based techniques, sometimes aided by bioassays (crossing breeding studies). Available molecular markers for its detection in mites include, but not limited to, the 16S ribosomal RNA (16S rRNA) and the Gyrase B (gyrB) (Hoy & Jeyaprakash 2005;Chigira & Miura 2005;Liu et al 2006;Novelli et al 2007;Enigl & Schausberger 2007;Novelli et al 2008;Chen et al 2009;Moro et al 2009b;Jeong et al 2009;Ros et al 2012;Zhu et al 2012b;Zhao et al 2013a;Zhao et al 2013b;Hubert et al 2012;Famah Sourasson et al 2014). The other techniques used to determine the presence and distribution of Cardinium in mites are transmission electron microscopy (Kitajima et al 2007) and fluorescence in situ hybridization (Zhu et al 2012a).…”
Section: Cardinium Prevalence In Mitesmentioning
confidence: 99%
“…It was found that Wolbachia and Cardinium maintain prevalence within many arthropod taxa by implementing a variety of reproductive manipulations (6). Although Wolbachia and Cardinium are transmitted maternally, both taxa or their genes have been found to be transmitted horizontally among spider mites (7). More recently, horizontal Wolbachia transfer between Drosophila melanogaster stocks facilitated by Tyrophagus putrescentiae has been reported; moreover, this transmission occurred through the ingestion of Wolbachia in infested corpses (8).…”
mentioning
confidence: 99%